Sejarah kemunduran fiqih, masa kebangkitan, serta pembaharuan fiqih - Pur, Fatima Daeng Tiri (Maliki Interdisciplinary Journal, 2026)
This article discusses the historical decline, revival, and reform of fiqh within the dynamic development of Islamic law. Fiqh, as an essential component of Islamic teachings, regulates various aspects of Muslim life, including worship, social transactions, and community affairs. Following the golden era of the great madhhab imams in the 2nd to 4th centuries Hijri, the development of fiqh experienced stagnation marked by the dominance of taqlid (blind adherence) and the perceived closure of the gate of ijtihad. Political instability, the fall of major Islamic intellectual centers, sectarian fanaticism, and the separation between religious and rational sciences were among the primary factors contributing to this decline. Prior to this period, fiqh flourished during the Umayyad and Abbasid eras, witnessing the emergence of major schools of law such as Hanafi, Maliki, Shafi‘i, and Hanbali, which enriched the methodological foundations of usul al-fiqh. In the 18th and 19th centuries, reform movements emerged in response to prolonged stagnation and modern challenges. Reformist scholars advocated reopening the gate of ijtihad, returning to the Qur’an and Sunnah, and applying the maqasid al-shariah approach to address contemporary issues